2014
DOI: 10.1002/ana.24264
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities and hypobaric exposure

Abstract: Objective Demonstrate that occupational exposure to nonhypoxic hypobaria is associated with subcortical white matter hyperintensities (WMHs) on fluid-attenuated inversion recovery magnetic resonance imaging (MRI). Methods Eighty-three altitude chamber personnel (PHY), 105 U-2 pilots (U2P), and 148 age- controlled and health-matched doctorate degree controls (DOC) underwent high-resolution MRI. Subcortical WMH burden was quantified as count and volume of subcortical WMH lesions after transformation of images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…However, these conditions are unlikely to be maintained throughout the life of longer longitudinal or cross‐sectional studies where scanner upgrades, significant hardware changes such as changes head coil, and other methodological changes may be expected. To address these aspects of longitudinal studies, our group and others used two strategies to accommodate for methodological changes: collections of calibration data and use of meta‐ and mega‐analyses (Jahanshad et al., 2013; Kochunov et al., 2015; McGuire et al., 2014a). In the first approach, calibration data are collected before and after change to derive cross‐calibration parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these conditions are unlikely to be maintained throughout the life of longer longitudinal or cross‐sectional studies where scanner upgrades, significant hardware changes such as changes head coil, and other methodological changes may be expected. To address these aspects of longitudinal studies, our group and others used two strategies to accommodate for methodological changes: collections of calibration data and use of meta‐ and mega‐analyses (Jahanshad et al., 2013; Kochunov et al., 2015; McGuire et al., 2014a). In the first approach, calibration data are collected before and after change to derive cross‐calibration parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐five (20 males/5 females, average age 25.8 ± 6.4 range 18–41 years) healthy subjects without hypertension, hyperlipidemia, or diabetes meeting USAF Flying Class III neurological standards were recruited (McGuire et al., 2014a,b). All subjects were in a military training environment with a consistently maintained meal time, sleep/wake time, and exercise program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute mountain sickness scores were higher, 34 and visual sensitivities were lower 35 in hypobaric than in normobaric hypoxia. Studies on U-2 pilots showed that hypobaria was associated with a change of white matter hyperintensity 14,36 and with the reduction of cortical thickness. 15 Moreover, exposure to hypobaria after traumatic brain injury worsened brain function.…”
Section: Effects Of Environmental Factors On Brain Structural Developmentioning
confidence: 99%
“…11,12 Hypobaria at a HA could also be a factor contributing to brain lesions because it has been proved to induce white matter and cortical thickness impairment. [13][14][15] Environmental ultraviolet rays can cause neuronal damage in the visual system and brain. [16][17][18] Therefore, these HA environmental factors together could have exerted their effect on brain development.…”
mentioning
confidence: 99%